O17.6 Parents'/healthcare providers' knowledge, attitude and perception of school-based HPV vaccination program in lagos, nigeria. (14th July 2019) - Adejimi, Adebola; Onasanya, Monsurat; Akodu, Babatunde
Abstract : Background: Human Papillomavirus(HPV) infection is a necessary cause for cervical cancer. HPV vaccine is available at a cost but not yet implemented in the national vaccination program in Nigeria. School age children are the target population for this vaccine. Parents play crucial roles in the decision to vaccinate their children against HPV and the healthcare providers have important roles to play in the coverage of this vaccine. The study objective was to assess and compare the knowledge, attitude and perception of parents and healthcare providers about school-based HPV vaccination program in Lagos State, Nigeria. Methods: A comparative cross sectional descriptive study involving 300parents of children aged 9–13 years attending public primary and junior secondary schools as well as 221healthcare providers in Primary Health Centers in Lagos State selected by multistage sampling techniques was conducted. A pre-tested self-administered questionnaire was used for data collection. Data analysis was done using SPSS. Chi-square statistics was used to test the associations between the variables at the level of significance of 5%. Results: The mean ages were 42.0±7.9 years (parents) and 36.8±6.2 years (healthcare providers). Majority of the parents (75%) and healthcare providers (94%) have heard of HPV infection and cervical cancer but only 40% of parents and 80% of the healthcare providers knew about HPV vaccine. Of these, 33% of the parents and 58% of the healthcare providers knew that this vaccine can be given in schools. Overall knowledge was significantly poor(35%) among parents and good(94%) among healthcare providers. Attitude and perception in both groups were good (about 90%) and about 70% of respondents were in support of school-based HPV vaccination. Significant factors affecting overall knowledge in the two groups were age, gender and level of education. Conclusion: With poor knowledge among parents, there is a need for educational campaigns and medical education to increase the HPV vaccine awareness with subsequent increase in vaccination coverage in Nigeria. Disclosure: No significant relationships.